2020
DOI: 10.21203/rs.3.rs-106340/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Screening and molecular characterization of cholesterol-lowering lactic acid bacteria isolated from African oil palm wine (Elaeis guineensis) and corn beer.

Abstract: Background: High serum cholesterol is a risk factor for cardiovascular disease (CVD), leading to many fatalities. Probiotic supplementation improves health benefits by lowering serum cholesterol. African oil palm (Elaeis guineensis) wine and corn beer have been described as potential sources of probiotic bacteria, but their cholesterol lowering activity has not been extensively investigated. Therefore in this study, we isolated and characterized lactic acid bacteria with probiotic and cholesterol lowering prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Similar inhibitory responses had been reported against diarrhoeagenic pathogens such as Salmonella typhi, Shigella dysentariae, Staphylococcus aureus and E. coli, compared to known antibiotics using a 7-day old fermented Raphia wine 83 . The responses observed may not be unconnected with the increased concentrations of metabolic products of wine fermentation such as lactic acid, acetic acid, alcohol, fatty acids and antimicrobial substances (bacteriocin, reutericyclin, mitoxantrone) known for their anti-microbial, immune-modulatory, anti-diabetic, anti-cancer, and cardio-circulatory functions 32,64,80,139,142,143 . The production of short-chain fatty acids particularly lactic and acetic acid by the LABs and AABs induces an unfavourable micro-environment inimical to the survival of intestinal pathogens through gut pH reductions 144,145 .…”
Section: Alcoholsmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar inhibitory responses had been reported against diarrhoeagenic pathogens such as Salmonella typhi, Shigella dysentariae, Staphylococcus aureus and E. coli, compared to known antibiotics using a 7-day old fermented Raphia wine 83 . The responses observed may not be unconnected with the increased concentrations of metabolic products of wine fermentation such as lactic acid, acetic acid, alcohol, fatty acids and antimicrobial substances (bacteriocin, reutericyclin, mitoxantrone) known for their anti-microbial, immune-modulatory, anti-diabetic, anti-cancer, and cardio-circulatory functions 32,64,80,139,142,143 . The production of short-chain fatty acids particularly lactic and acetic acid by the LABs and AABs induces an unfavourable micro-environment inimical to the survival of intestinal pathogens through gut pH reductions 144,145 .…”
Section: Alcoholsmentioning
confidence: 97%
“…Yeast isolates from palm wine have shown strong antimicrobial activities against pathogenic organisms such as Staphylococcus aureus, Pseudomonas aeruginosa and Klebsiella spps. 139,140 . A study by Ojo and Agboola 141 , observed that fermented palm wine of Raphia vinifera and Elaeis guineensis had an inhibitory effect against Salmonella typhi compared to antibiotic drugs like chloramphenicol, amoxicillin, Gentamicin and ciprofloxacin.…”
Section: Alcoholsmentioning
confidence: 99%